Use of ICT in Vital Event Registration in Nepal and its Implementation Challenges - Paudel, Sanjeet; Shakya, Subarna (Journal of Advanced College of Engineering and Management, 2018)
To improve service delivery of government, paper based vital event registration (VER) system should gradually be replaced by ICT based system. This paper highlights the barriers that may stand in implementing ICT in VER. Questionnaire was used to collect primary data. Population size for the research was 6,743 out of which 272 valid responses were used for the research. The gathered data were subjected to demographic study, T-test, ANOVA test and Reliability analysis. The correlation between independent and dependent variables were computed. It was found that nine constructs namely: cost, leadership and management support, organizational process and commitment, usability, human factor, system feature, infrastructure, acts, rules and regulations and political situation are major barriers for implementing ICT based system for vital event registration.